Application of a Robust Image Hashing Technology - Jadhav Vishwajeet Narayanrao ,Vullanki Rajesh (Journal of Computational Analysis and Applications (JoCAAA), 2024)
The proliferation of digital image manipulation tools has fundamentally challenged thetrustworthiness of visual media. Traditional cryptographic hash functions (e.g., SHA-256,MD5) are brittle: a single bit flip in the image file produces a completely different hash, rendering them useless for content-based integrity verification.